Bangkit Untuk Berprestasi: Studi Fenomenologis Pada Atlet Penyandang Disabilitas Personel TNI di Pusat Rehabilitasi Kementerian Pertahanan Republik Indonesia - Wahyu Firdaus; Sokhivah Sokhivah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Achievement in sports is generally associated with athletes who have a healthy and perfect physique. However, physical perfection is no longer the main requirement because now many individuals with physical disabilities have become athletes and have succeeded in increasing their existence as inspiring figures. This research was conducted with the aim of understanding the meaning of life for TNI athletes with physical disabilities who are able to excel in sports. This research method is qualitative phenomenological through interviews, observation and documentation. The research results show that the process of rising from adversity to become a path to achievement consists of data on perceptions of the meaning of life as an athlete with a disability, social support, negative experiences, and motivation.